Obyknovennyi prezident . Ordinary President - Khashevatsky, Jury (Belarus, 1996)
The film is dedicated to Mikhail Romm, the director of the famous Soviet documentary "Ordinary fascism," which is also referred to in the title. Combining the footage shot in the grounds of Auschwitz and voice-over speeches of the infamous Belarusian leader Alexander Lukashenko, the film makes a powerful case against the ideological leanings and affinities of the president. Allowing Lukashenko to muse unabashed about the "rise and prosperity of Germany under the wise rule of Hitler" as a supposed model to emulate, the director delivers an uncanny indictment of the oppressive regime established by Lukashenko and the dangerous implications of the rhetoric he adopted. The director Jury Khashevatsky, internationally known filmmaker and a prominent member of Belarus' Helsinki committee had the opportunity to experience the nature of Lukashenko's regime first-hand. Soon after the release of the movie and its screening in Germany, he was attacked and badly beaten by an "unidentified mob" and after that was continuously threatened and intimidated by the police and the special service. The film was shown only once by a provincial private channel, the members of the TV crew were detained and interrogated or fired after the broafcast. "The Ordinary President" is still officially banned in Belarus. The film was officially banned from public screening in Belarus.